Limited Bedding and Nesting Induces Maternal Behavior Resembling Both Hypervigilance and Abuse - Gallo, Meghan; Shleifer, Daniel G.; Godoy, Livea D.; Ofray, Dayshalis; Olaniyan, Aliyah; Campbell, Talia; Bath, Kevin G. (Frontiers in Behavioral Neuroscience, 2019)
Early life adversity (ELA) is associated with altered neural development and increased risk for the development of psychopathology across the lifespan. Rodent models of ELA are an important tool for investigating the possible mechanistic underpinnings of pathology development. We used a limited bedding and nesting model (LBN) to induce stress in the dam and alter dam-pup interactions during a sensitive period in early postnatal development. The primary characteristics previously identified in this model include fragmented and unpredictable maternal care and possibly neglect. However, previous studies have not consider the effects of this manipulation over the full circadian cycle and the evolution of changes of maternal behavior throughout the duration of the manipulation. In the current study, we leverage a novel continuous video monitoring setup to unobtrusively observe and subsequently analyze maternal behaviors. Through this more in depth analysis, we discovered that LBN dams spent more time than control dams on their nest, returned to their nest more frequently than control dams, and showed intact maternal care. Importantly, a subset of LBN dams (~40%) engaged in abusive-like kicking, a behavioral pattern not previously identified in this paradigm. Exposure to ELA and abusive-like kicking were associated with differences in risky-taking like behavior in adulthood. The LBN model of ELA may drive a more complex constellation of effects on maternal behavior, driving a pattern of increased dam-pup interactions and increased abuse-like kicking behavior, with unique consequences for pup outcomes.